Pengaruh Kompensasi Terhadap Kinerja Perawat Honorer Di Rumah Sakit Umum Majene - Zakib, Muh; Malik, Ihyani; Parawu, Hafiz Elfiansyah (Universitas Muhammadiyah Makassar, 2021)
This study purposed to determine how the views of honorary nurses and patients about the eligibility of receiving compensation for honorary nurses at Majene General Hospital. This type of research used descriptive quantitative method, the population in this study were honorary nurses at the general hospital in the district of Majenene, which amounted to 477 honorary nurses (if the population was smaller than the sample then all were examined (saturated / census sample. This study used three data collection techniques were observation, questionnaire and documentation, while the data analysis used questionnaire, data presentation and conclusion. The results showed that the effect of work motivation (x) on employee performance (y) based on regression testing found that the H_0 was rejected and H_1 accepted so that it was found that compensation affects the performance of honorariums in the Majene area general hospital, most agree with the compensation given to nurses to improve the performance of honorary nurses.This study purposed to determine how the views of honorary nurses and patients about the eligibility of receiving compensation for honorary nurses at Majene General Hospital. This type of research used descriptive quantitative method, the population in this study were honorary nurses at the general hospital in the district of Majenene, which amounted to 477 honorary nurses (if the population was smaller than the sample then all were examined (saturated / census sample. This study used three data collection techniques were observation, questionnaire and documentation, while the data analysis used questionnaire, data presentation and conclusion. The results showed that the effect of work motivation (x) on employee performance (y) based on regression testing found that the H_0 was rejected and H_1 accepted so that it was found that compensation affects the performance of honorariums in the Majene area general hospital, most agree with the compensation given to nurses to improve the performance of honorary nurses.